Relation between the depth of tumor and neck node metastasis in early carcinoma of tongue - Kshirsagar, Pankaj; Manerikar, Kshitij Arun (International Surgery Journal, 2018)
Background: Tongue squamous cell carcinoma (TSCC) is one of the aggressive forms of oral cancer with a high recurrence rate. Forty percentages of all TSCC patients have neck metastasis at the time of diagnosis. The status of cervical lymph nodes at presentation is the single most important prognostic factor in TSCC. This study was focused on establishing relation between the tumor depth and neck node metastasis in carcinoma of tongue. Authors accessed the patterns of cervical node metastasis in it. Methods: prospective non-randomised study of 100 patients was carried out. After detail clinical history punch biopsy were taken from the tongue lesion. Biopsy proven cases of early squamous cell carcinoma (T1/T2) with clinically negative neck (cN0) were included in this study. Ultra-sonography of the tongue using 7.5 MHz probe was performed in all cases to know the depth of lesion. Final histopathological findings i.e. pT, pN, differentiation and depth of invasion were compared with pre-operative clinical and radiological findings. Results: Out of 100 patients, 62 were males and 38 were females. Clinically 56 patients were belonged to T2. Ultra-sonography of tumor had high sensitivity and specificity. Node positivity increased with the depth of primary tumor. On histopathological examination, positive node observed in total 25 patients. Number of occult neck node positivity raised with increased size of primary tumor. i.e. 15% and 31% with pT1 and pT2, respectively. Level II was the most common site for cervical node involvement followed by level III. Conclusions: Ultra-sonography was a reliable tool to access the depth of tumor pre-operatively in the cases of tongue carcinoma patients with sensitivity and specificity more than 90%. Node positivity increased with the depth of primary tumor. Tumor thickness is a significant predictor of nodal metastasis and elective neck dissection should be decided accordingly.